Enhanced mass transfer in air oscillating in a channel with periodically varying radius. (March 2021) - Kozlov, V.; Polezhaev, D.
Highlights: Air oscillations enhance contaminant mass transfer in a channel with varying radius In a channel with varying radius, air oscillations create a steady streaming motion Increase of a channel radius variation results in enhancement of steady flow velocity Abstract: The effect of high frequency oscillations of air column in a channel of variable radius on vapor diffusion is experimentally studied. It is found that significant enhancement of longitudinal mass transfer takes place due to steady vortical flows excited in channel cells. In parallel with experiments in air we conducted PIV experiments with low viscous fluids in order to study the steady flow structure in the same range of dimensionless frequency as in diffusion experiments with air. It is revealed that additional mass transfer Ds associated with the steady flow is a function of steady flow dimensionless velocity V, which depends on frequency ω and pulsating Reynolds number. It is followed from PIV measurements that Ds ∼ V 2 and in the studied range of oscillation frequency ω, the additional diffusion rate D s is an order larger than the molecular diffusion D . Comparison of our experimental data with data of other authors obtained in the experiments with channels of another geometry shows that increase of variation of a channel radius results in significant enhancement of steady flow velocity and, therefore, mass transfer.